Soil depth constraints in the revegetation of reclaimed coal mine land - WAHJUNI HARTATI; SYAHRINUDIN SYAHRINUDIN; TRIYONO SUDARMADJI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Hartati W, Syahrinudin, Sudarmadji T. 2024. Soil depth constraints in the revegetation of reclaimed coal mine land. Biodiversitas 25: 1838-1845. Plants require adequate root space, nutrients, water, and air for optimal growth. This study analyzed the relationship between plant growth (i.e., diameter) and soil properties (i.e., thickness, organic matter content, texture) on revegetated post-coal mining land in East Kalimantan, Indonesia. Field research was conducted at revegetated area primarily planted with four species (Hibiscus tiliaceus, Enterolobium cyclocarpum, Samanea saman and Acacia sp.) with age of 8 years. Data was collected from 30 plots of 0.05 ha. Plant diameter were recorded and soil samples were taken from 0-10, 10-30, and >30 cm depths using soil auger at three points per plot. Organic matter content was determined by the Walkley-Black method, and texture by the Pipette method. Multiple regression analysis was used to used to investigate the relationship between plant diameter and soil properties. The study found that different species showed varying correlations between soil properties and growth. Acacia sp. and S. saman exhibited strong correlations (r=0.78), while E. cyclocarpum had a low correlation (r=0.35), and H. tiliaceus a moderate one (r=0.49). Soil thickness had a stronger influence on H. tiliaceus (?=0.05) and S. saman (?=0.01) than other tested properties. For some species, diameter growth was primarily determined by soil thickness in the revegetated area. The study highlights the importance of considering species-specific soil requirements for successful revegetation and plant growth on post-coal mining sites.